1985
DOI: 10.1111/j.2044-8279.1985.tb02627.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender Salience and Social Identity: The Impact of Sex of Siblings on Educational and Occupational Aspirations

Abstract: SUMMARY.It is proposed that an understanding of sex differences in educational and occupational aspirations of adolescents would benefit from a perspective which stresses gender identification. The social identification approach (Turner, 1982) hypothesises that these differences are a function of the degree of gender identification, which in turn is a function of the salience of sex. According to McGuire and McGuire's (1981) distinctiveness postulate, gender becomes more salient as the number of opposite sex s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…However, when the sex-role ideology of subjects is known, gender salience may be predictive of endorsement of attitudes which support that ideology (both in ad hoc and real long-term settings; cf. Abrams et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when the sex-role ideology of subjects is known, gender salience may be predictive of endorsement of attitudes which support that ideology (both in ad hoc and real long-term settings; cf. Abrams et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…household decreased, spontaneous mention of gender increased. However, Abrams, Sparkes & Hogg (1985) found that the direction and magnitude of effects of different sex ratios in the home did not directly reflect the distinctiveness which those ratios might be presumed to confer. Of particular interest was the finding that females' sex-stereotypical aspirations were related only to their number of brothers, while males' sex-stereotypical aspirations were most related to their number of sisters.…”
Section: Dominic Abramr Joanne Thomaj and Michael A Hoggmentioning
confidence: 91%
See 1 more Smart Citation
“…The recall of school marks was more stereotype-consistent in a condition of high salience than in a condition of low salience of gender stereotypes . Gender stereotypes are known to become more salient whenever gender identity is primed (e.g., Ambady et al 2001;Guimond and Roussel 2001) or made salient in socialization contexts (Abrams et al 1985(Abrams et al , 1990, a fact that accentuates stereotypic self-perceptions (related to being a girl or a boy) (Deaux 1985;Guimond et al 2006;Lorenzi-Cioldi and Doise 1994). Based on this, we hypothesized that salience of gender identity should accentuate the effects of gender stereotypes on girls' and boys' self-perceptions.…”
Section: Self-perceptions In Mathematicsmentioning
confidence: 96%
“…Biological factors may impose restrictions and predispositions on gender in girls and boys, but contextual factors are influential determinants. Context can render gender categories salient or not, increasing or decreasing gender identification, and may or may not lead to one or another set of gendered beliefs and behaviors (Abrams, Sparkes, & Hogg, 1985; Abrams, Wetherell, Cochrane, Hogg, & Turner, 1990). Indeed, the magnitudes of a range of gender differences appear to vary impressively across cultures and nations (Lucas & Gohm, 2000; Williams & Best, 1990).…”
Section: Gender Theory and Gender Similarities And Differencesmentioning
confidence: 99%